Reversible Loss of Hippocampal Function in a Mouse Model of Demyelination/Remyelination - Das, Aniruddha; Bastian, Chinthasagar; Trestan, Lexie; Suh, Jason; Dey, Tanujit; Trapp, Bruce D.; Baltan, Selva; Dana, Hod (Frontiers in Cellular Neuroscience, 2020)
Demyelination of axons in the central nervous system (CNS) is a hallmark of multiple sclerosis (MS) and other demyelinating diseases. Cycles of demyelination, followed by remyelination, appear in the majority of MS patients and are associated with the onset and quiescence of disease-related symptoms, respectively. Previous studies in human patients and animal models have shown that vast demyelination is accompanied by wide-scale changes to brain activity, but details of this process are poorly understood. We used electrophysiological recordings and nonlinear fluorescence imaging from genetically-encoded calcium indicators to monitor the activity of hippocampal neurons during demyelination and remyelination over a period of 100 days. We found that synaptic transmission in CA1 neurons was diminished in vitro, and that neuronal firing rates in CA1 and the dentate gyrus (DG) were substantially reduced during demyelination in vivo, which partially recovered after a short remyelination period. This new approach allows monitoring how changes in synaptic transmission induced by cuprizone diet affect neuronal activity, and it can potentially be used to study the effects of therapeutic interventions in protecting the functionality of CNS neurons.